Paranoplocephala alaskensis Haukisalmi & Henttonen, 2007, n. sp. ... - Haukisalmi, Voitto; Henttonen, Heikki (Zenodo, 2007)
Paranoplocephala alaskensis n. sp. (Fig. 5) Type host: Microtus miurus, Myomorpha, the singing vole. Type locality: Fortress Mountain, Gates of the Arctic National Park and Preserve (GAAR), northern Alaska, U.S.A., 68o34'19.7"N, 152o57'20.9"W. Site: Small intestine (duodenumn or jejunum). Deposited specimens: Holotype: MSB Endo 14 (field code AF 61775), from Microtus miurus (UAM 78448), collected on 30th July 2002 at Fortress Mountain, Gates of the Arctic National Park and Preserve (GAAR), northern Alaska, U.S.A. (68o34'19.7"N, 152o57'20.9"W). Collectors: H. Henttonen, K. Hildebrandt, J. Laakkonen and J. Niemimaa. Paratype: MSB Endo 15 (AF 61754), from Mi. miurus (UAM 78403), collected on 29th July 2002 at Fortress Mountain, GAAR, Alaska (68o34'48.4"N, 152o57'35.6"W). Collectors as for the holotype. Voucher specimens (all from Mi. miurus from Alaska): i) MSB Endo 17 (AF 58231, UAM 82045), Easter Creek near Lake Tulilik, GAAR, ii) MSB Endo 19 (AF 58239, UAM 82046), Lake Tulilik, GAAR, iii) MSB Endo 21 (AF ... : Published as part of Haukisalmi, Voitto & Henttonen, Heikki, 2007, A taxonomic revision of the Paranoplocephala primordialis (Douthitt) complex (Cestoda: Anoplocephalidae) in voles and squirrels, pp. 51-68 in Zootaxa 1548 on pages 62-64, DOI: 10.5281/zenodo.178029 ...